Demonstrasi Mahasiswa “Tolak Reformasi Dikorupsi” Dalam Agenda Media Tirto.Id - Muchammad Abdul Ghofur; Herru Prasetya Widodo; Asra Bulla Junga Jara Jara; Fathul Qorib (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
ABSTRACT The online media Tirto.id presents a new face for reporting in Indonesia as relaxed, in-depth, and full of data. As a new media, Tirto.id has become one of the media that counts in Indonesia. Its peculiarity can be seen from its various news related to the government, including the news about student actions rejecting the KPK Law and the revision of the KUHP Law. This study aimed to reveal the media agenda of Tirto.id in reporting the demonstration titled #ReformasiDikorupsi and #GejayanMemal using the Agenda Setting theory. There were 14 news on Tirto.id from 18 September 2019 to 30 September 2019 were analyzed using the concepts of the Setting Agenda, namely visibility, audience salience, and valence. As a result, Tirto.id showed its support for the #ReformasiDikorupsi demonstration in various news sections, from the title, photo captions, and the content of the news. Tirto.id showed in its reporting that the government was negligent and so it was opposed by students who are positioned as 'people's representatives'. This research concluded that Tirto has a special agenda to reject the KPK Law and the amendments to the Criminal Code Law (KUHP) through news dictions to the selection of news sources. Tirto tried to monitor the government through his in-depth coverage Keywords: Media Agenda, Corruption Reform, Tirto.id, Student Demonstrations